Vietnam : Technical Assistance Report-Government Finance Statistics (June 10-14, 2019). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
The main purpose of the mission was to continue TA to assist with upgrading the compilation and dissemination of fiscal data and GFS in Vietnam in line with the international standard, the Government Finance Statistics Manual 2014 (GFSM 2014).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet